Familial multinodular goiter and Sertoli-Leydig cell tumors associated with a large intragenic in-frame DICER1 deletion. Issue 2 (February 2018) - Apellaniz-Ruiz, Maria; de Kock, Leanne; Sabbaghian, Nelly; Guaraldi, Federica; Ghizzoni, Lucia; Beccuti, Guglielmo; Foulkes, William D
Abstract : Objective: Familial multinodular goiter (MNG), with or without ovarian Sertoli-Leydig cell tumor (SLCT), has been linked to DICER1 syndrome. We aimed to search for the presence of a germline DICER1 mutation in a large family with a remarkable history of MNG and SLCT, and to further explore the relevance of the identified mutation. Design and methods: Sanger sequencing, Fluidigm Access Array and multiplex ligation-dependent probe amplification (MLPA) techniques were used to screen for DICER1 mutations in germline DNA from 16 family members. Where available, tumor DNA was also studied. mRNA and protein extracted from carriers' lymphocytes were used to characterize the expression of the mutant DICER1. Results: Nine of 16 tested individuals carried a germline, in-frame DICER1 deletion (c.4207-41_5364+1034del), which resulted in the loss of exons 23 and 24 from the cDNA. The mutant transcript does not undergo nonsense-mediated decay and the protein is devoid of specific metal ion-binding amino acids (p.E1705 and p.D1709) in the RNase IIIb domain. In addition, characteristic somatic 'second hit' mutations in this region were found on the other allele in tumors. Conclusions: Patients with DICER1 syndrome usually present a combination of a typically truncating germline DICER1 mutation and a tumor-specific hotspot missense mutation within the sequence encoding the RNase IIIb domain. The in-frame deletion found in this family suggests that the germline absence of p.E1705 and p.D1709, which are crucial for RNase IIIb activity, may be enough to permit DICER1 syndrome to occur.